FIB-4 index is associated with hepatocellular carcinoma risk in HIV-infected patients. - Park, Lesley S; Tate, Janet P; Justice, Amy C; Lo Re, Vincent; Lim, Joseph K; Bräu, Norbert; Brown, Sheldon T; Butt, Adeel A; Gibert, Cynthia; Goetz, Matthew Bidwell; Rimland, David; Rodriguez-Barradas, Maria C; et al. (Cancer epidemiology, biomarkers & prevention : a publication of the American Association for Cancer Research, cosponsored by the American Society of Preventive Oncology, 2011)
Chronic inflammation caused by hepatitis B virus infection, hepatitis C virus infection, and/or heavy alcohol use can lead to fibrosis, cirrhosis, and eventually hepatocellular carcinoma (HCC). FIB-4 is an index score calculated from platelet count, alanine transaminase, aspartate transaminase, and age that predicts fibrosis and cirrhosis. We hypothesized that high FIB-4 would be associated with development of HCC in HIV-infected persons, who are at high risk due to high prevalence of viral hepatitis and alcohol consumption, and possibly due to HIV infection itself.
Keywords: Adult; Age Factors; Aged; Alanine Transaminase; Aspartate Aminotransferases; Biological Markers; Carcinoma, Hepatocellular; Cohort Studies; Female; HIV Infections; Humans; Liver Function Tests; Liver Neoplasms; Male; Middle Aged; Platelet Count; Risk Factors